A Survey: Space Vector PWM (SVPWM) in 3φ Voltage Source Inverter (VSI) - Shalini Vashishtha; K.R. Rekha (Institute of Advanced Engineering and Science, 2018)
Since last decades, the pulse width modulation (PWM) techniques have been an intensive research subject. Also, different kinds of methodologies have been presented on inverter switching losses, inverter output current/ voltage total harmonic distortion (THD), inverter maximum output of DC bus voltage. The Sinusoidal PWM is generally used to control the inverter output voltage and it helps to maintains drive performance. The recent years have seen digital modulation mechanisms based on theory of space vector i.e. Space vector PWM (SVPWM). The SVPWM mechanism offers the enhanced amplitude modulation indexes (MI) than sinusoidal PWM along with the reduction in the harmonics of inverter output voltage and reduced communication losses. Currently, the digital control mechanisms have got more attention than the analog counterparts, as the performance and reliability of microprocessors has increased. Most of the SVPWM mechanisms are performed by using the analog or digital circuits like microcontrollers and DSPs. From the recent study, analysis gives that use of Field Programmable Gate Arrays (FPGA) can offer more efficient and faster solutions. This paper discusses the numerous existing research aspects of FPGA realization for voltage source inverter (VSI) along with the future line of research.